Effects of a nanoceria fuel additive on the physicochemical properties of diesel exhaust particles - J.J. Zhang; Lee, K. B.; He, L.; Seiffert, J.; Subramaniam, P.; L. Yang; S. Chen; Maguire, P.; Mainelis, G.; Schwander, S.; Tetley, T.; Porter, A.; et al. (Environ Sci Process Impacts, 2016)
Nanoceria (i.e., CeO2 nanoparticles) fuel additives have been used in Europe and elsewhere to improve fuel efficiency. Previously we have shown that the use of a commercial fuel additive Envirox in a diesel-powered electricity generator reduced emissions of diesel exhaust particle (DEP) mass and other pollutants. However, such additives are currently not permitted for use in on-road vehicles in North America, largely due to limited data on the potential health impact. In this study, we characterized a variety of physicochemical properties of DEPs emitted from the same engine. Our methods include novel techniques such as Raman spectrometry for analyzing particle surface structure and an assay for DEP oxidative potential. Results show that with increasing Envirox concentrations in the fuel (0x, 0.1x, 1x, and 10x of manufacturer recommended 0.5 mL Envirox per liter fuel), DEP sizes decreased from 194.6 +/- 20.1 to 116.3 +/- 14.8 nm; the zeta potential changed from -28.4 mV to -22.65 mV; DEP carbon content decreased from 91.8% to 79.4%; cerium and nitrogen contents increased from 0.3% to 6.5% and 0.2% to 0.6%, respectively; the ratio of organic carbon (OC) to elemental carbon (EC) increased from 22.9% to 38.7%; and the ratio of the disordered carbon structure to the ordered carbon structure (graphitized carbon) in DEPs decreased. Compared to DEPs emitted from 0x, 0.1x, and 1x fuels, DEPs from the 10x fuel had a lower oxidative potential likely due to the increased ceria content because pure ceria nanoparticles exhibited the lowest oxidative potential compared to all the DEPs. Since the physicochemical parameters tested here are among the determinants of particle toxicity, our findings imply that adding ceria nanoparticles into diesel may alter the toxicity of DEPs. The findings from the present study, hence, can help future studies that will examine the impact of nanoceria additives on DEP toxicities.
Keywords: Air Pollutants/*analysis; Carbon/analysis; Cerium/*chemistry; gasoline; Metal Nanoparticles/*chemistry; Particle size; Particulate Matter/*analysis; Vehicle Emissions/*analysis